Bibliographic title search for medical cardiological "signs" (eponyms). (22nd September 2018) - Kanie, Takayoshi; Mizuno, Atsushi; Kawai, Fujimi; Iri, Takanobu; Suzuki, Takahiro; Oshima, Shinichirou; Fukui, Sho; Son, Raku; Matsuo, Takahiro
Abstract: Background: The word "sign" refers to important physical findings or observations that are useful in diagnosis; however, there are no scientific reviews of "signs." The aim of this paper was to list and review these terms using a bibliographic approach. Methods: We performed a title search of "sign" using a bibliographic search and review approach in MEDLINE and EMBASE. Results: We detected 398 papers including 217 medical signs in cardiology. Conclusions: This is the first literature review of eponyms specifically for signs using a bibliographic method, which is useful for the discussion of the appropriateness of eponyms. Abstract : Bibliographic search strategies. We finally detected 398 articles and 217 signs from MEDLINE and EMBASE.